A STUDY OF RHETORICAL DEVICES IN TITLES OF ONLINE TOURISM NEWSPAPERS IN ENGLISH VERSUS VIETNAMESE - Phạm Thị Phương Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis studied rhetorical devices in titles of online tourism newspapers in English and Vietnamese. An analysis was made to find out the commonly used rhetorical devices and point out the similarities and differences between them in English and Vietnamese titles of online tourism newspapers. The data of this study were collected from two online newspapers in English and Vietnamese namely Travel Daily News and Du Lich. The data were descbribed and contrastively analyzed on stylistic aspects under qualitative and quantitative approaches. On the basis of a contrastive analysis, the thesis tried to find out commonly used rhetorical devices in English and Vietnamese titles of online tourism newspapers, namely metaphor, metonymy, simile, personification, rhetorical questions, stylistic inversion, enumeration, alliteration, and rhyme. The analysis was based on 400 samples (200 in English and 200 in Vietnamese), which were collected from popular and prestigiuos online toursim newspapers in English and Vietnamese. On the basis of the findings, this thesis set out some implications and suggestions for teaching and learning both languages. The research result could be useful for teachers, copywriters, freelancers and learners of English, as well as those who are interested in tourism, linguistics and language in use.